ANALYSIS OF WORKERS CHARACTERISTIC AND HISTORY OF DISEASE WITH PULMONARY FUNCTION STATUS IN LIMESTONE BURNING INDUSTRIAL IN TUBAN REGENCY EAST JAVA INDONESIA - Ramadiani, Ning Gusti (International Journal of Psychosocial Rehabilitation, 2020)
Limestone industry is one of the industries that contributes to the occurrence of considerable air pollution. Limestone dust burning has a major effect on workers such as pulmonary function disorders both acute and chronic. To analyze workers characteristic and history of disease with pulmonary function status in limestone burning industrial in tuban regency east java indonesia This research was an observational study with cross sectional design. The sample size in this study was 18 workers. The measurement of pulmonary function status in workers was done using a spirometer. Data analysis was perfomed descriptively from crosstab results by looking at coefficient contingency dengan melihat nilai coefficient contingency value:There were 11.1% of workers who had abnormal pulmonary function status, with details of 1 worker (5.55%) had pulmonary function impairments with light restriction and obstruction categories, 1 another worker (5.55%) had pulmonary function impairments with moderate restriction and obstruction categories. From the results of cross tabulation, there was less means correlation between working period with pumonary function status (0,039), there was weak correlation between nutritional status with pumonary function status (0,186), age with pumonary function status (0,205), smoking habits with pumonary function status (0,271). There was very strong correlation between history of disease with pulmonary function status with coefficient contingency (0,707). Workers who experienced abnormal pulmonary function status are workers who have a history of the disease, followed by workers who have smoking habits. Even though the workers relatively young (